Utilization of Dietary Maggot Frass on the Performance, Carcass Percentage, Digestive Organs, and Economic Value of Muscovy Ducks - Utama, C. S.; Cahya, R. I.; Sulistiyanto, B. (Faculty of Animal Science, IPB University, 2024)
This study aimed to examine the effect of using maggot frass level inclusion in the diet on the performance, digestive organs, immune organs, and economic value of Muscovy Ducks. The study employed a completely randomized design with four treatments and five replications. The treatments used were: T0= 100% basal feed, T1= 80% basal feed + 20% maggot frass, T2= 60% basal feed + 40% maggot frass, and T3= 40% basal feed + 60% maggot frass. This study involved 300 Muscovy ducks aged 4 days, weighing 40.52 ± 4.81 gram/bird, and spanning a rearing period of 8 weeks. The obtained data was subjected to analysis of variance, followed by Duncan’s test (p<0.05) for significance. The results showed that the increase in body weight, final weight, IOFDC, N retention, and carcass percentage decreased along with increasing maggot frass content. There was an increase in feed consumption, AME, TME, and crude fiber digestibility when giving maggot frass. There is a tendency for performance to decrease as the percentage of maggot frass in duck feed increases, but maggot frass can still be used at a percentage of 40%. Based on the study’s findings, the use of maggot frass up to 40% can reduce feed operational costs and positively affect the IOFDC value.